2004
DOI: 10.1007/s00213-004-1777-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific effects of scopolamine on canine cognition: Impairment of visuospatial memory, but not visuospatial discrimination

Abstract: Working memory performance is most sensitive to scopolamine-induced impairment and can be dissociated from scopolamine-induced deficits in discrimination performance and non-cognitive behaviors. The present results indicate that scopolamine-induced impairments of working memory in the dog can serve as a model of age-related cholinergic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
(61 reference statements)
2
23
0
Order By: Relevance
“…The scopolamine model is frequently used in preclinical studies of cognitive impairment. Studies in animals showed that scopolamine induced memory impairments similar to those seen in humans [11][12][13]. Scopolamine has been used in humans for several different purposes, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The scopolamine model is frequently used in preclinical studies of cognitive impairment. Studies in animals showed that scopolamine induced memory impairments similar to those seen in humans [11][12][13]. Scopolamine has been used in humans for several different purposes, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Previously we provided evidence of cholinergic involvement in canine cognition by examining the effect of scopolamine on performance of a delayed non-matching to position task (DNMP) and found working memory performance in aged dogs was disrupted by a 15 μg/kg dose of scopolamine, which produced no obvious behavioral effects [49]. By contrast, young dogs were not impaired by the same scopolamine dose [50] and showed higher muscarinic receptor density than aged dogs [51].…”
Section: Introductionmentioning
confidence: 99%
“…The P2 delay was also induced in normal subjects by the administration with anti-cholinergic drugs [2]. Araujo et al [1] demonstrated that the cholinergic system was also important in cognitive deficits in dogs. Therefore, the delay of the latency of P2 and the later peaks observed in aged dogs might be reflected the neurological disturbance with the defects of neurotransmitter.…”
mentioning
confidence: 98%